A realist evaluation case study of the implementation of advanced nurse practitioner roles in primary care in Scotland. (18th April 2022) - Strachan, Heather; Hoskins, Gaylor; Wells, Mary; Maxwell, Margaret
Abstract: Aim: To evaluate Advanced Nurse Practitioner (ANP) role implementation in primary care across Scotland in contributing to primary care transformation, and establish what works, for whom, why and in what context. Design: A realist evaluation using multiple case studies. Methods: Two phases, conducted March 2017 to May 2018: (1) multiple case studies of ANP implementation in 15 health boards across Scotland, deductive thematic analysis of interviews, documentary analysis; (2) in‐depth case studies of five health boards, framework analysis of interviews and focus groups. Results: Sixty‐eight informants were interviewed, and 72 documents were reviewed across both phases. ANP roles involved substitution for elements of the GP role for minor illness and injuries, across all ages. In rural areas ANPs undertook multiple nursing roles, were more autonomous and managed greater complexity. Mechanisms that facilitated implementation included: the national ANP definition; GP, primary care team and public engagement; funding for ANP education; and experienced GP supervisors. Contexts that affected mechanisms were national and local leadership; remote, rural and island communities; and workload challenges. Small‐scale evaluations indicated that ANPs: make appropriate decisions; improve patient access and experience. Conclusions: At the time of the evaluation, the implementation of ANP roles in primary care in Scotland was in early stages. Capacity to train ANPs in a service already under pressure was challenging. Shifting elements of GPs workload to ANPs freed up GPs but did little to transform primary care. Local evaluations provided some evidence that ANPs were delivering high‐quality primary care services and enhanced primary care services to nursing homes or home visits. Impact: ANP roles can be implemented with greater success and have more potential to transform primary care when the mechanisms include leadership at all levels, ANP roles that value advanced nursing knowledge, and appropriate education programmes delivered in the context of multidisciplinary collaboration.